2010
DOI: 10.4314/njbas.v18i1.56869
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Activity in Fermented Oil Seeds of Africa Locust Bean, (Parkia Biglobosa), Castor Seeds (Ricinu Communis) and African Oil Bean (Pentaclethra Macrophylla).

Abstract: ABSTRACT:The activity of lipase in fermented Africa locust bean, Castor seed, and Africa oil bean was determined. The peak lipase activity for fermented Africa locust bean, Castor seed, and African oil bean were 13.3x10 -3 µmol/sec, 7.2 x10 -3 µmol/sec and 10.6 x10 -3 µmol/sec at day 5, 4 and 4 respectively. The optimum temperature and pH were 30 0 C and 7.0 respectively for all the fermented seeds above. Increasing NaCl concentration decreases the activity of Lipase indicating that NaCl is an inhibitor of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It is expected that the longer the period of fermentation (4-5 days), the better the product, due to more activities of the fermenting bacterial flora, but period of fermentation is another major difference in the method of traditional production of Iru, because nowadays most of the fermentation times are usually one to three days instead of four to five days. The result obtained in this research corroborates with the study of Liman et al (2010) who demonstrated the impacts of some environmental conditions on quality of processed locust beans.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is expected that the longer the period of fermentation (4-5 days), the better the product, due to more activities of the fermenting bacterial flora, but period of fermentation is another major difference in the method of traditional production of Iru, because nowadays most of the fermentation times are usually one to three days instead of four to five days. The result obtained in this research corroborates with the study of Liman et al (2010) who demonstrated the impacts of some environmental conditions on quality of processed locust beans.…”
Section: Discussionsupporting
confidence: 82%
“…It is deciduous perennial tree that grows to between 7 and 20 m high. In some cases, up to 30 m (Ntui et al, 2012). The tree is a fire-resistant helophyte characterized by a thick dark gray-brown bark (Abioye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A work by [8] posits that the seed is a good source of lipase. AOB seed improves metabolism and possess anti-atherogenic property [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research Liman et al, (2010), found that lipase from Africa locust bean, Castor seed, and Africa oil bean has an optimum pH 7. Similarly, Pratiwi et al, (2013) …”
Section: Effect Of Phmentioning
confidence: 99%